AMELIORATION OF ANXIOLYTIC BEHAVIOR IN INTRACEREBROVENTRICULAR COLCHICINE INJECTED RATS BY NAPROXEN - SIL, SUSMITA; GHOSH, TUSHARKANTI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Anxiety behavior in experimental model of Alzheimer's disease (AD) in rats by intracerebroventricular (ICV) injection of colchicine is important to characterize this animal model, but it has not been sufficiently investigated in this animal model. The different attributes of anxiety behavior in ICV colchicine injected rats (ICIR) was studied, and the effects of naproxen, a non-steroidal anti-inflammatory drug on the anxiety status of these AD animals were assessed since in earlier studies naproxen protected cognitive impairments and neurodegeneration in ICIR. Methods: The anxiety status was assessed in an elevated open field with a novel object in two study durations (14-day and 21-day study). After measuring the anxiety behavior in two study durations, rats were sacrificed, and blood was collected for measuring the serum corticosterone (CORT) level. Results: Anxiolytic behavior along with lower CORT level was observed in ICIR in both the 14- and 21-day studies. After p.o. administration of different doses of naproxen (5, 10, 20 mg/kg body wt.) in ICIR, this anxiolytic behavior along with low serum CORT level showed gradual recovery and eventually both the parameters attained normal level at the dose of 20 mg/kg body weight in 21-day study. Conclusion: The present study showed an anxiolytic behavior in ICIR, and which may result from the colchicine induced neurodegeneration along with the impaired activity of the hypothalamo-pituitary-adrenal axis. Some parameters appeared to be sensitive for determination of anxiety status in this model. Keywords: Colchicine, Anxiolytic, Naproxen, Corticosterone, Alzheimer's disease.